Nondestructive Analysis of Wall Paintings at Ostia Antica - Bernhard Blümich; Eleonora Del Federico; Denis Jaschtschuk; Markus Küppers; Katelin Fallon; Adelaide Steinfeld; Paolo Tomassini (Heritage, 2021)
Roman wall paintings at Ostia Antica were studied for the first time in situ in an integrated approach using nuclear magnetic resonance (NMR) depth profiling, portable X-ray fluorescence (XRF), and visible induced luminescence (VIL) in order to explore the materials used in their construction and gain insight into the evolution of the Roman painting technique over time. NMR revealed the signatures of covered wall paintings through details of the structure of the top painted mortar layers, and the loss of this information that can be encountered when paintings are detached from the wall for preservation purposes. XRF provided information about the pigment composition of the paintings, and VIL was used to identify Egyptian Blue. Egyptian Blue was only found in the earlier wall paintings studied dating from 1st century B.C.E. to the 1st century C.E. The pigment palette seems to become limited to iron-based pigments in the later paintings, whereas the palette of the earlier paintings appears to be more varied including mercury, lead, and copper-based pigments.